Landscape for architects = Landschaft für Architekten = Paisaje para arquitectos - Kiefer, Gabriele G.; Neubauer, Anika; Kiefer, Gabriele G.; Kiefer, Gabriele G.; Kiefer, Gabriele G. (Basel, Switzerland : Birkhäuser Verlag Gmbh, 2020)
Designing gardens, parks and landscapes requires a holistic approach. It also requires extensive specialist knowledge. In courses and manuals the generalist or in-depth levels are frequently under-represented, or the attempted comprehensive view becomes too complex. "Landscape for Architects" now offers a fundamental reference work which is as comprehensive as it is practical and as holistic as it is detailed. Created in cooperation with the Architecture Department of Braunschweig Technical University, Landscape for Architects addresses the aspects of landscape architecture: "questions" are raised with abstract schematic drawings, and possible "answers" are illustrated with analytical drawings of case studies from the 20th and 21st centuries in order to inspire the reader?s own creativity and to support the design process. The entire field of landscape design is dealt with in individual thematic volumes. The numbers of pages in the volumes differ, adding up to a total of 1000 pages in five volumes, which are published as packages with clear color marking: the "green block" with the first five volumes in the autumn of 2018, the second and final one, also with five volumes, in the autumn of 2019. Each volume fully covers the respective subject and can be used on its own?compact and user-friendly. The illustrations are uniformly structured, with the guiding idea on the left-hand side and the associated drawing on the right-hand side. The drawings demonstrate how design concepts can be illustrated, and the three-language format provides an international vocabulary of design.
[Volume 1]. Building -- [volume 2]. Landscape -- [volume 3]. Park -- [volume 4]. Use -- [volume 5]. Qualities.
In English with most content also in German and Spanish.
Title from wrapper.
boek
Keywords: Landscape architecture -- Miscellanea; Landscape design -- Miscellanea; Landscape architecture; Landscape design